To defend or to attack? Antagonistic interactions between Serratia plymuthica and fungal plant pathogens, a species-specific volatile dialogue - Rybakova, Daria; Müller, Henry; Olimi, Expedito; Schaefer, Angelika; Cernava, Tomislav; Berg, Gabriele (Frontiers in Sustainable Food Systems, 2022)
Volatile organic compounds (VOCs) are involved in interspecies communication and in the mode of action of various antagonistic interactions. They are important for balancing host-microbe interactions and provide the basis for developing biological control strategies to control plant pathogens. We studied the interactions between the bacterial antagonist Serratia plymuthica HRO-C48 and three fungal plant pathogens Rhizoctonia solani, Leptosphaeria maculans and Verticillium longisporum. We observed significant differences in fungal growth inhibition by the Serratia-emitted VOCs in pairwise dual culture assays and changes in the transcriptome of the bacterium and in the volatilomes of both interacting partners. Even though the rate of fungal growth inhibition by Serratia was variable, the confrontation of bacterium with the VOCs of all three fungi changed the levels of expression of the genes involved in stress response, biofilm formation, and the production of antimicrobial VOCs. Pairwise interacting microorganisms switched between defence and attack modes, subject to the combinations of microorganisms that were interacting. HRO-C48 significantly inhibited the growth of R. solani in the attack mode, while simultaneously boosting its own metabolism. By contrast, its metabolism was downregulated when HRO-C48 went into a defence mode that was induced by the L. maculans and V. longisporum VOCs. L. maculans growth was slightly reduced by the one bacterial VOC methyl acetate that induced a strong downregulation of gene expression in S. plymuthica. Similarly, the interaction between S. plymuthica and V. longisporum resulted in an insignificant growth reduction of the fungus and repressed the rate of bacterial metabolism, accompanied by an intense volatile dialogue. Overall, our results indicate that VOCs substantially contribute to the highly species-specific interactions between pathogens and their natural antagonists and thus deserving of increased consideration for pathogen control.